The Development of Integrated Scientific Process Skills by Using Active Learning for Grade 11 Students - Jitpreeda, Lapaspon; Phorntaweekul , Satjatham (Journal for Developing the Social and Community, 2023)
This research aims to develop integrated scientific process skills. using proactive learning activities for grade 11 students, 70% passed the criteria. The research process was based on Kurt Lewin’s action research concept. The target group was 21 grade 11 students. The research tools were the learning management plan by Use proactive learning activities Integrated Science Process Skills Assessment Form field record form and a semi-structured interview The data were analyzed by percentage, mean and the data obtained from the field recording were analyzed, compiled and presented in an essay format. The results showed that A total of 21 students, representing 100%, achieved a score of 70% or higher on the Integrated Science Process Skills assessment.